Financial inclusion and financial well-being among youth: a systematic scoping review - Avnner Chardles Wellfren; Roslaini Abdul Jalil; Nelson Lajuni; Izaan Azyan Abdul Jamil (Inderscience Enterprises Ltd, 2025)
This research aimed to comprehensively explore the relationship between financial inclusion and financial well-being among youth, focusing on financial inclusion. Employing a systematic scoping review methodology, this study examined a broad spectrum of scholarly works to identify existing knowledge gaps and provide insightful recommendations for future research. The research findings suggested that financial inclusion exhibited an inconsistent direct effect on financial well-being; however, it played a notable role as a supplementary factor. It is imperative to acknowledge that the effective utilization of financial inclusion necessitated the cultivation of appropriate skills, attitudes, and behaviors to fully harness its potential advantages in enhancing financial well-being. These results serve as a foundational reference for future research, offering insights into the current state of the topic. Lastly, the study aimed to raise awareness within communities and government agencies about the importance of enhancing the social well-being and happiness of young people.